2005 IEEE Antennas and Propagation Society International Symposium
DOI: 10.1109/aps.2005.1552312
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the Bandwidth in Terminal Antennas by Tuning the Coupling between the Element and its Ground

Abstract: Introduction. The intensive research on terminal antennas last years examined new ideas that resulted in the formulation of guidelines on how specific antenna parameters could be accomplished. Among the few more challenging variables in obtaining parameters, two gained our particular attention: a broad bandwidth and a radiation pattern that does not produce SAR values exceeding the permissible level. Broadening the bandwidth at the lowest resonance in multiresonant antennas featuring the highest possible scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The utilization of a slotted ground plane for broadening operational bandwidth of a small terminal antenna was described in [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of a slotted ground plane for broadening operational bandwidth of a small terminal antenna was described in [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, it was shown that the bandwidth of the antenna-PCB combination has an important dependency on the PCB resonant wavemode and on the coupling between the antenna and the PCB. Some antennas were designed subsequently, taking this idea as a starting point [2,3]. However, in the handset PCB there exists not a single resonant mode but several ones, which can be computed by means of the Theory of Characteristic Modes (TCM) [4] and used to improve the handset radiating properties.…”
Section: Introductionmentioning
confidence: 99%
“…Planar antennas are mostly suitable for these applications due to their compact size and impedance bandwidth that is continuously widened by using various techniques. A simple square planar monopole is shown to have a ratio impedance bandwidth of 2:1, which has been greatly enhanced by using an offset feeding point, a semicircular base [1], a shorting post and beveling technique [2], a technique with double or three feeds [3], and so forth. In [4], a printed elliptic patch juxtaposed with a ground pattern in a single substrate was presented, where the impedance bandwidth was enhanced by using a new impedance-matching technique of cutting a notch in the ground pattern opposite the microstrip line.…”
Section: Introductionmentioning
confidence: 99%
“…Gain (dBi) Efficiency (%) Figure 6.37 Gain (dBi) and efficiency (%) vs. frequency. Moreover, in order to further improve the impedance matching level, some authors have proposed the insertion of slots in the PCB [162]- [163], as shown in Figure 6.39. This slot not only produce a meandering effect that contributes to reduce the resonant frequency of horizontal modes, but it also changes the current distribution of these modes near the excitation point, favoring the coupling between them and the feeding source.…”
Section: Wideband Feeding Of the Mobile Handset Pcbmentioning
confidence: 99%